The Street As a Living Space (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
The crisis of the public space in the ‘modern’ city has a history that goes a long way back, and such crisis is intrinsic to the mutation itself of the city and to the practice of planning of the modern city, which does not in fact, build any public space on the outside of a building. Little to nothing is elaborated to produce spaces of communal gathering which could be compared, even vaguely so, to the ancient agorà.In recent history, dwellings keep on being the main topic subjected to transformation and experimentation, while the considerations on the outdoor space as instrument aimed to organize social life are still very few.Amongst the numerous researches only few are addressed to the potential influence that open space could have in organizational terms, and on the relationships that it could generate, like the one that the Austrian architect, Bernard Rudofsky, will develop.The motive that associates the series of exhibitions presented and curated by Rudofsky at MoMA in New York is the proposition of the street as a collective place. Rudofsky’s works, research and exhibitions anticipate the awkwardness of the contemporary urban landscape, which generally excludes life outside the buildings, starting a process in which, paradoxically, contemporary city architecture is more and more a private business which belongs to the client and the architect who is not anymore responsible towards everybody. Rudofsky, by introducing a vast repertoire of communal spaces, like streets, arcades, lodges, stairwells, puts together a catalogue of possibilities and demonstrates in what measure and how such elements of construction of the city could have a fundamental role in the living space.